The effects of macroprudential policies on house price cycles in an agent-based model of the Danish housing market - Graeme Cokayne (Danmarks Nationalbank, 2019)
Following the global financial crisis, many countries have introduced or tightened macroprudential policies. Using an agentbased model (ABM), this paper seeks to measure the impact on house price cycles of two distinct borrower-based macroprudential instruments, namely loan-to-income and loan-to-value ratios. The use of an ABM allows for the consideration of the effects of these policies on the distribution of heterogeneous households. The paper shows that the relation between tightening an instrument and its effect on house price fluctuations may be highly non-linear, depending on the distribution of households for which the instrument becomes binding. Furthermore, the paper demonstrates that the marginal effect of tightening one instrument generally depends on the calibration of the other instrument. From a policy perspective, these findings highlight the importance of using granular data - preferably at the household level - when calibrating borrower- based macroprudential instruments. Likewise, the findings demonstrate the importance of macroprudential authorities establishing a coherent framework where the effects of different measures are evaluated together.
Keywords: D1; D31; E58; G18; G21; R2; R21; R31; 330; Housing; Agent-based model; Macro-prudential Policies; Regulation